Peter Wickham letter to Carl Bendorf, June 2 1991 - Wickham, Peter P.et al (1991)
Letter from Peter Wickham to Carl Bendorf on June 2, 1991, summarizing his spring birding. Included with the letter is a field notes form that includes detailed notes on specific sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1991. Epson - sheet feed/flatbed